Estudo do polimorfismo rs7895833 no gene SIRT1 e sua associação com diferentes comorbidades de idosos atendidos no ambulatório de geriatria de um hospital universitário da região central do Brasil - Casarotto, Andréia Athayde Firmiano (2018)
SIRT1 is a human protein belonging to the sirtuin family. It plays the role of histone deacetylase causing gene silencing and also targets the deacetylation of key proteins involved in the body's metabolic and adaptive response mechanism. The SIRT1 gene is a single copy gene located in the chromosome 10. Polymorphisms in this gene have been studied in works involving aging, seeking an association between genetic variants, metabolic diseases and longevity. Objectives: To determine the allelic and genotypic frequency of the rs7895833 A / G polymorphism in the SIRT1 gene and to identify the association between this polymorphism and prevalent comorbidities, functional and cognitive status in the elderly sample. Methods: 230 elderly patients treated at the geriatric outpatient clinic of the Júlio Müller University Hospital in Cuiabá, Mato Grosso, Brazil were evaluated. Of these, 216 completed the study were submitted to standardized interview and validated application, blood collection for laboratory tests. The DNA extraction was done by the salting out technique and the genotyping by the PCR-CTPP technique with two pairs of primers. Results: The majority of the sample was female (57.4%), mean age was 69.32 (SD:6,81) years, 44.9% of the patients were white, 44% brown, and 11% black. The prevalence of systemic arterial hypertension was 74.1%, diabetes mellitus 25.0%, dyslipidemia 81.6%, obesity 28.7% and 32.9% were overweight. The frequency of polymorphism rs7895833 in the SIRT1 gene in the sample was: AA (56/216) 25.9%, AG (138/216) 63.9% and GG (22/216) 10.2%. The frequency of allele A was 0.58 and of the allele G 0.42. In the multivariate analysis of the exploratory variables glucose, HDL cholesterol, have systemic arterial hypertension, dyslipidemia and depression associated with the polymorphism rs7895833 in the univariate analysis, only have dyslipidemia showed a statistically significant difference with a greater number of individuals with dyslipidemia in patients with genotype AA, (p = 0.020). Conclusion: The results showed a frequency of the minor allele (G) of 0.42. Studies show that the frequency of the variant allele changes according to the studied population. The associations found suggest that individuals with polymorphism rs7895833 may present differences in the control of lipid metabolism.